The Effects of Quotas on Vertical Intra-Industry Trade - Stefan H. Lutz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
A quota on foreign competition will generally lead to quality-upgrading (downgrading) of the low-quality (high-quality) firm, an increase in average quality, a reduction of quality differentiation, and a reduction of domestic consumer surplus, irrespective of whether the foreign firm produces higher or lower quality. Effects of a quota on industry profits and domestic welfare depend crucially on the direction of international vertical differentiation. If the foreign firm produces low quality, both firms' prices and profits rise but domestic welfare falls. This describes well some major effects of a Japanese VER in the US auto market and relevant empirical findings. If the foreign firm produces high quality, foreign profits will fall. Since domestic consumer surplus falls only unsubstantially, domestic profit gains lead to an increase of domestic welfare.
Keywords: F12; F13; L13; 330; trade; quotas; vertical product differentiation; quality-dependent costs; Außenhandelskontingent; Exportbeschränkung; Intraindustrieller Handel; Duopol; Produktqualität; Internationaler Wettbewerb; Wohlfahrtseffekt; Theorie